The Effect of Sports Massage and Acupressure on Lactic Acid Levels, Physical and Psychological Fatigue, and the Effect on Nurse Performance - Prasetya, Fika Indah; Hartono, Soetanto; Wahyuni, Endang Sri; Muhammad, Heryanto Nur; Tyas, Eka Suryaning; Sasmito, Priyo (International Journal of Public Health Excellence (IJPHE), 2023)
Background: The increasing number of elderly service users in nursing homes and the small number of geriatric specialist nurses have made nurses who work in nursing homes vulnerable to burnout. Therefore, it's crucial to develop methods to anticipate and overcome burnout in geriatric nurses, particularly through non-pharmacological approaches. Purpose: The purpose of this study is to analyze the effect of sports massage and acupressure on lactic acid levels, physical and psychological fatigue, and nurse performance. Method: A quantitative research was carried out with a quasi-experimental approach. The study population comprised nurses working at the Tresna Wredha Social Institution (TWSI). The sample included 30 participants, selected through a total sampling technique, and divided into three groups. The collected data was analyzed using ANOVA. Results: A total of 30 nurses participated in the study. After receiving the intervention, the sports massage group showed the lowest lactic acid levels at 2.7 mmol/L, the lowest physical fatigue with an average value of 25.0, and the highest performance score with an average value of 135.0. The results of statistical calculations indicate a relationship between sports massage and acupressure with outcomes (lactic acid levels, physical and psychological fatigue, and nurse performance) with a p-value of less than 0.05. Additionally, the Pairwise Comparison test found that sports massage is more effective than acupressure in reducing lactic acid levels and physical and psychological fatigue. Conclusion: The study shows that sports massage and acupressure significantly decrease lactic acid levels and physical/psychological fatigue, and can improve the performance of nurses. Furthermore, sports massage is more effective than acupressure in achieving these outcomes.